Short- and long-term quality of life after electrical cardioversion of atrial fibrillation. (3rd October 2022) - Morken, I; Ponitz, V; Brugger-Andersen, T; Aareskjold, O; Aadnanes, L; Melberg, T; Bru, E; Nordrehaug, J E
Abstract: Background: Electrical cardioversion (ECV) of atrial fibrillation (AF) is known to be effective in restoring sinus rhythm. However, limited and contradictory data exist on the impact of ECV on short- and long-term quality of life outcomes. Purpose: To examine the impact of ECV on short- and long-term quality of life in patients with AF. Methods: This was a prospective cohort study of consecutive patients with AF referred for outpatient electrical cardioversion at a university hospital in Norway. Recruitment started March 2017, and ended December 2019. Baseline demographics, clinical characteristics, and procedure details were obtained from medical records. Quality of life was measured with the Atrial Fibrillation Effect on Quality of Life (AFEQT) questionnaire before electrical cardioversion (baseline), and at three and 12 months after ECV. Results: Two hundred and ninety-five patients underwent ECV and completed follow-up questionnaires at three months (n-259) and at 12 months (n=258). The median age was 68 years (range 37–86 years) and 79% were men. The mean left ventricular ejection fraction obtained by echocardiography was 51% (±9.2). The mean body mass index score was 28±4.8. Immediate success of electric cardioversion was 91%. Recurrence of AF after successful ECV was 36% within three months. Twenty-two percent of the patient underwent new ECV before three months, and 25% of the patients had persistent AF at three months. The overall mean AFEQT score at baseline was 62.9±21.4, and the domain-specific scores were as follows: symptoms, 72.3±23.1; daily activities, 52±26.6; treatment concerns, 71.1±22.4; and treatment satisfaction, 59.9±25.2. There were significant improvements in the overall mean AFEQT score at three months, 70.8±20.8, (p<0.01) and at 12 months, 72.3±20.8 (p<0.01) compared with baseline values. There were also significant improvement (p<0.01) in all AFQET subscales at three and 12 months. Daily activity scores and treatment satisfactions scores demonstrated highest improvement in mean score with a 10% increase from baseline to three months and 13% increase from baseline to 12 months. Sub-analyses revealed that patients with persistent AF within three months were significantly dissatisfied with treatment (p<0.01) and reported lower activity level (p<0.01) compared with the rest of the sample. Conclusions: Results indicate both significant improvement in short- and long-term quality of life for patients after electrical cardioversion, in particular when sinus-rythm was maintained. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Stavanger University Hospital